Analysis of mainland Japanese and Okinawan Japanese populations using the precision ID Ancestry Panel. (March 2018) - Nakanishi, Hiroaki; Pereira, Vania; Børsting, Claus; Yamamoto, Toshimichi; Tvedebrink, Torben; Hara, Masaaki; Takada, Aya; Saito, Kazuyuki; Morling, Niels
Highlights: 165 AIMs were typed in 49 mainland Japanese and 47 Okinawa Japanese using the Precision ID Ancestry Panel. One locus had statistically significantly different genotype frequencies in the two samples, after Bonferroni correction. The population likelihoods for mainland Japanese and Okinawa Japanese were not significantly different from each other. STRUCTURE and PCA showed that the panel could not differentiate mainland Japanese, Okinawa Japanese, and East Asians. Abstract: We typed 165 AIMs in 49 mainland Japanese and 47 Okinawa Japanese using the Precision ID Ancestry Panel (Thermo Fisher Scientific). None of the 165 SNPs showed significant deviation from Hardy-Weinberg equilibrium in the mainland Japanese. One SNP (rs3943253) showed significant deviation from Hardy-Weinberg equilibrium in Okinawa Japanese. Fisher's exact tests showed that the genotype frequencies of 14 loci were significantly different (p < 0.05) between the two populations before correction for multiple testing. After Bonferroni correction, only rs671 remained statistically significant (p < 0.0003). This SNP is located in the ALDH2 gene. The mutant A allele is associated with increased side effects after alcohol intake. The frequency of the GG genotype (wild type) was higher in the Okinawa Japanese (78.7%) than in mainland Japanese (34.7%; Bonferroni corrected P < 0.001). For 31 (63.3%) of the mainland Japanese and 42 (89.4%) of Okinawa Japanese, the highest population likelihood was obtained with the Japanese reference population. However, only in a few individuals, the likelihoods were significantly different from those calculated using reference data from neighboring populations. The likelihoods for mainland Japanese and Okinawa Japanese were not significantly different from each other for any of the investigated individuals. STRUCTURE and PCA analyses showed that mainland Japanese, Okinawa Japanese, and East Asians could not be differentiated with the Precision ID Ancestry Panel.